Caracterización de la geometría de fracturas hidráulicas en función de la evaluación de distintas metodologías para el cálculo de presión de poro en diferentes ambientes de sobrepresión (2021)
The behaviour of a hydraulic fracture is affected by factors inherent to its geomechanics, such as, Young’s modulus, Poisson’s ratio, the properties of the fracture fluid and the pore pressure. It has been noted by some authors that the latter, seems to have a direct influence on the geometry of said fracture, as well as, its incidence on the in-situ stress and its propagation throughout its medium. The aim of this work is the evaluation of the effect of the pore pressure on the geometry of a fracture performed on the well “A”, located in the Upper Magdalena Valley Basin (Colombia).